A clinically‐relevant residue of POLR1D is required for Drosophila development. Issue 11 (16th June 2022) - Palumbo, Ryan J.; Belkevich, Alana E.; Pascual, Haleigh G.; Knutson, Bruce A.
Abstract: Background: POLR1D is a subunit of RNA Polymerases I and III, which synthesize ribosomal RNAs. Dysregulation of these polymerases cause several types of diseases, including ribosomopathies. The craniofacial disorder Treacher Collins Syndrome (TCS) is a ribosomopathy caused by mutations in several subunits of RNA Polymerase I, including POLR1D. Here, we characterized the effect of a missense mutation in POLR1D and RNAi knockdown of POLR1D on Drosophila development. Results: We found that a missense mutation in Drosophila POLR1D (G30R) reduced larval rRNA levels, slowed larval growth, and arrested larval development. Remarkably, the G30R substitution is at an orthologous glycine in POLR1D that is mutated in a TCS patient (G52E). We showed that the G52E mutation in human POLR1D, and the comparable substitution (G30E) in Drosophila POLR1D, reduced their ability to heterodimerize with POLR1C in vitro . We also found that POLR1D is required early in the development of Drosophila neural cells. Furthermore, an RNAi screen revealed that POLR1D is also required for development of non‐neural Drosophila cells, suggesting the possibility of defects in other cell types. Conclusions: These results establish a role for POLR1D in Drosophila development, and present Drosophila as an attractive model to evaluate the molecular defects of TCS mutations in POLR1D. Key Findings: POLR1D is required for Drosophila larval growth and developmental progression. A conserved glycine in POLR1D is required for Drosophila and human development. Loss of POLR1D function in Drosophila neural cells causes developmental defects. An RNAi screen reveals a requirement for POLR1D function in the proper development of a variety of cell types Drosophila is an attractive model to evaluate the genetic and molecular defects of TCS mutations in POLR1D.